2004
DOI: 10.1007/bf02991051
|View full text |Cite
|
Sign up to set email alerts
|

A new sediment contact assay to assess particle-bound pollutants using zebrafish (danio rerio) embryos

Abstract: A new sediment contact assay to assess particle-bound pollutants using zebrafish (Danio rerio) embryos. Soils and Sediments, http://dx.doi.org/10.1065/jss2003.09.085 Journal ofAccess to the published version may require subscription. Conclusions.A modified protocol of the zebrafish embryo test allows the assessment of sediment toxicity in both aqueous extracts and native sediments. The isolated investigation of pore waters may result in a clear-cut underestimation of the bioavailability of lipophilic part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 20 publications
0
47
0
6
Order By: Relevance
“…SPM extracts were also toxic when sampled at mean annual discharge directly after the flood event but became less toxic thereafter. Hollert et al (2003bHollert et al ( , 2007a showed that SPM from the 1998 flood event at the Neckar (HQ=20) caused NR 50 values for RTG-2 cells between 20-and 60-mg/mL test medium. These results were comparable to the toxicity caused by the 2004 flood SPM assessed in this study.…”
Section: Cytotoxic Effects Of Complex Samplesmentioning
confidence: 98%
“…SPM extracts were also toxic when sampled at mean annual discharge directly after the flood event but became less toxic thereafter. Hollert et al (2003bHollert et al ( , 2007a showed that SPM from the 1998 flood event at the Neckar (HQ=20) caused NR 50 values for RTG-2 cells between 20-and 60-mg/mL test medium. These results were comparable to the toxicity caused by the 2004 flood SPM assessed in this study.…”
Section: Cytotoxic Effects Of Complex Samplesmentioning
confidence: 98%
“…Even though the MariETT is a laboratory-based assay focusing on toxicological endpoints of a selected model species, future application is envisaged to include testing of ''natural'' samples such as stream water or sediment interstitial water. Similar to the zebrafish, Danio rerio embryo toxicity test (DarT) which also has started as a pure toxicological test with single substances but now is even used for natural sediment assessment (Hollert et al 2003;Hallare et al 2005a, b;Wu et al 2010), we see a great potential of the MariETT for ecotoxicological application in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Sediments represent one of the ultimate sinks for organic and inorganic contaminants including heavy metals discharged into environment (Bettinetti et al 2003;Hollert et al 2003;Luoma and Bryan 1981). Sediments also play a significant role in the remobilization of contaminants (Zhigang and Gao 2007).…”
Section: Introductionmentioning
confidence: 99%